Newcastle disease control in Kibwezi District, Kenya: Comparing different methods of vaccination delivery - Wyatt, Amanda; Grace, Delia; Alders, Robyn G.; Bagnol, B.; Young, M.; Msami, H.; Lindahl, Johanna F. (2014)
In spite of the availability of Newcastle disease vaccines, uptake by smallholder farmers is generally limited and Newcastle disease remains a major constraint to village poultry keeping in developing countries. This report presents findings from a study on the factors affecting uptake and use of the Newcastle disease vaccine in Kibwezi District, Kenya. Villages where the supply of the vaccine is supported by the Farm Input Promotions Africa (FIPS-Africa) organisation were compared to villages where the organisation is not active. Our results indicate that a supportive vaccine delivery system can encourage Newcastle disease vaccine use and reduce chicken mortality; farmers who had used the vaccine had an average flock size that was 3 chickens larger than farmers who had never used the vaccine. Even so, Newcastle disease vaccine demand and uptake would be improved in the study area by increasing the perceived effectiveness of the vaccine, addressing concerns about affordability, and following a vaccination calendar. Findings from our study suggest that the sustainable vaccine delivery model used by FIPS-Africa in Kibwezi District can promote awareness, knowledge, proper administration, and continued use of the Newcastle disease vaccine.